Linguistic description of eponymy: parameters and problems - Yermolenko, S.S. (Мовознавство, 2018)
The article deals with theoretical and methodological aspects of the model for eponymy description and analysis. Establishing the set of parameters for such a model as well as outlining issues in applying them, it discusses these questions within the general framework of the study of onomastic items’ secondary use to denote objects other than their primary referents.